2000
DOI: 10.1063/1.373791
|View full text |Cite
|
Sign up to set email alerts
|

Growth mode and surface morphology of a GaN film deposited along the N-face polar direction on c-plane sapphire substrate

Abstract: Articles you may be interested inPredominant growth of non-polar a-plane (Al,Ga)N on patterned c-plane sapphire by hydride vapor phase epitaxy J. Appl. Phys. 113, 093505 (2013); 10.1063/1.4794098 Polarity determination of a-plane GaN on r -plane sapphire and its effects on lateral overgrowth and heteroepitaxy J. Appl. Phys. 94, 942 (2003); 10.1063/1.1578530 Comparative study of GaN and AlN nucleation layers and their role in growth of GaN on sapphire by metalorganic chemical vapor depositionThe dependence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
61
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 48 publications
2
61
0
Order By: Relevance
“…4,5 However, metalorganic chemical vapor deposition (MOCVD) growth of N-polar GaN on sapphire typically leads to the formation of a rough surface morphology with hexagonal pyramidal structures and lower crystalline quality than Ga-polar GaN. 6 Such hexagonal hillocks were also observed in homoepitaxial GaN layers grown on N-polar GaN bulk substrates by MOCVD. 7 Moreover, the growth on N-polar faces suffers from the significant incorporation of residual impurities such as oxygen, which leads to difficulties in controlling n-type and p-type conductivities.…”
mentioning
confidence: 98%
“…4,5 However, metalorganic chemical vapor deposition (MOCVD) growth of N-polar GaN on sapphire typically leads to the formation of a rough surface morphology with hexagonal pyramidal structures and lower crystalline quality than Ga-polar GaN. 6 Such hexagonal hillocks were also observed in homoepitaxial GaN layers grown on N-polar GaN bulk substrates by MOCVD. 7 Moreover, the growth on N-polar faces suffers from the significant incorporation of residual impurities such as oxygen, which leads to difficulties in controlling n-type and p-type conductivities.…”
mentioning
confidence: 98%
“…However, preparing N-polar GaN is more difficult, since the surface is more reactive. 25 To date there have been few published studies reporting the effects of different pretreatments on N-polar GaN. English et al 26 compared the surface morphology change of the N-polar GaN surface after various pretreatment method, but they did not report any the electrical properties of the ALD oxides nor did they correlate the effect of pretreatments.…”
mentioning
confidence: 99%
“…It becomes generally N polarity, but it sometimes becomes Ga polarity by annealing in N 2 atmosphere or by an appropriate growth conditions [2]. Anyway, GaN grown on these buffer layer continues their polarity and never change in the MOVPE growth [3]. However, in case of the HVPE growth, we reported that the intermediate layer on the N polarity buffer layer grown on the GaAs(111)B surface showed the Ga polarity [4].…”
mentioning
confidence: 94%